Internationalization, Diplomacy, and Beyond: Considering Studying Abroad as a Medium of Learning Through the Lens of Cultural Studies and Public Pedagogy - Sae Shimauchi (Education Sciences)
Studying abroad has been emphasised to increase the cultural influence of sending countries and promote international understanding. This study re-examines study abroad as part of the internationalisation of higher education, using concepts of soft power, knowledge diplomacy, public diplomacy, and cultural diplomacy. Specifically, the study highlights the limitations of the conceptual frameworks of ‘nation’ and ‘formal educational opportunities’ in studying abroad, and discusses a perspective on learning that goes beyond the physical space of the university and the formal educational opportunity. Furthermore, this study considers cultural studies and a public pedagogy perspective to examine where and how studying abroad and international learning can occur. Therefore, this research aims to provide a more interdisciplinary perspective on higher education research surrounding the phenomenon of studying abroad, and to examine the academic boundaries that define the field of research on the internationalisation of higher education. The paper concludes that studying abroad and international education should be reconsidered as a ‘medium’ that promotes cross-border learning by understanding culture and social structure.